PEMBERDAYAAN PRANATA SOSIAL MELALUI KOMUNIKASI LINGKUNGAN: MENAKAR PELIBATAN PERAN PEREMPUAN DALAM MITIGASI BANJIR CITARUM - Iriana Bakti; Hanny Hafiar; Heru Riyanto Budiana; Lilis Puspitasari (Jurnal Kawistara, 2017)
The study is titled implementation of environmental communication based on the social institution in coping with the flood in the Citarum Watershed Upstream. Citarum river pollution and silting are currently in a state of particular caused by forest encroachment in the upstream, land use, household waste, animal husbandry, industry, offices, etc, so when the rainy season caused the occurrence of floods. In addition, these conditions have resulted in water quality being unfit to be utilized, both for drinking water, washing, bathing, irrigation for agriculture and so on. The actuator environment seeks to restore the Citarum Watershed upstream conditions by building public awareness so they may want to change their attitudes and behavior, one of them by not disposing of waste into the river. The selected communities are those that are incorporated in a social institution in the region. The purpose of the research is to find out about the types of institution, the reason for utilizing the institution, and the role of the environment actuator communication in a social institution. The methods used in this research is descriptive with qualitative data to describe the various realities of communication activities related to the environment by leveraging social institution in coping with the disaster of the flood in the area of Citarum Watershed Upstream. Research results showed in the region there are four types of institutions, namely the institution of religious, economic, agricultural and social. Institution related to religious activity is Majlis Ta'lim (the place of informal Islamic teaching and education), institution related to the activity of the economy is an arisan (regular social gathering), institution related to social activity is the PKK (Family Welfare Guidance), and institution related to the agricultural activity is The Association of Farmers Group (Gapoktan). The reason for the environment actuator utilizing social institution are as the entrance (access) to carry out flood mitigation program, already familiar, easy to invited to cooperate and to expand the network. The role of the environment actuator in the institution as a communicator and facilitator in conducting dissemination of information and training of waste utilization to the members of the institutions.